PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI SEBAGAI UPAYA PENINGKATAN LAYANAN PERPUSTAKAAN BAGI PENYANDANG DISABILITAS - Winda Anestya Ayunda (Perpustakaan Nasional RI, 2017)
This study explains about the lack of disability-friendly libraries. Libraries should have been able to improve services to persons with disabilities. Moreover, technology has progressed. Tools and innovations to help people with disabilities are growing. Information and communication technology is needed as an effort to make it happen. This study used qualitative approach with descriptive method. The results showed that government and society are two major factors in the development of accessibility for persons with disabilities. The availability of technology will make it easier for people with disabilities to find information until it can be accessed by anyone.